Early discontinuation of intravenous antimicrobial therapy in pediatric oncology patients with febrile neutropenia - Grundy Paul E; Hodgson-Viden Heather; Robinson Joan L (BMC, 2005)
Abstract Background There are no standard criteria for when to discontinue intravenous antimicrobial therapy (IVAMT) in children with febrile neutropenia (FN), but it is now common to discontinue IVAMT and discharge patients with an absolute neutrophil count (ANC) ≤ 500 /mm3. The purpose of this study was to evaluate the outcome of a large cohort of children with FN who had IVAMT discontinued with an ANC ≤ 500 /mm3 Methods A retrospective chart review was completed of patients in the Northern Alberta Children's Cancer Program with FN and no apparent clinical source of fever from June 1, 1997 to July 1, 2002. Results Out of a total of 275 patients, 127 (46%) had at least one episode of FN, with FN occurring in patients with sarcomas more commonly than in those with leukemia/ lymphoma and least in those with other solid tumors. In 59 of 276 episodes of FN (21%) patients had a microbiologically defined infection at admission. Of the 217 remaining episodes, 112 of 199 patients (56%) with known neutrophil counts had IVAMT discontinued before their absolute neutrophil count (ANC) reached 500 /mm3 at the discretion of the clinician. Fever recurred in only two of these patients after discharge, and there were no bacterial infections diagnosed after parenteral antibiotics were discontinued. Conclusion Even without use of standard criteria for early discharge, clinicians appear to be skilled at selecting children with FN who can safely have IVAMT discontinued with an ANC ≤ 500 /mm3.